Clinicopathological Study of Mucormycosis in Post Covid Patients, an Epidemic in Pandemic - Divya Pujari Jayakeerthy; Pradeep Kumar Reddy Mereddy; Adicherla Govardhan; Seema Bijjaragi (Medical Laboratory Technology Journal, 2022)
Mucormycosis is an angio-invasive disease caused by saprophytic fungi of the order Mucorales. Mucormycosis has been established and recognized as a complication of the SARS-CoV-2 infection. Mucormycosis, well known as "black fungus" is creating an epidemic within a global pandemic. The use of different dose regimens, prominent steroids, and multiple comorbidities like Diabetes Mellitus and post-COVID could predispose to mucormycosis. The aim of the study was to study the increase in cases and morphological features of mucormycosis infection in hospitalized post-COVID patients. This prospective study was done for four months, from May 1st, 2021, to August 31st, 2021. All the suspected cases of mucormycosis specimens sent to the Department of Pathology, J.J.M. Medical College, Davangere, for histopathological diagnosis were considered. For microscopic examination, the collected samples were fixed in 10% formalin solution, processed, and stained with Haematoxylin and Eosin. Periodic Acid-Schiff special staining was done. Thirty cases of mucormycosis were collected from patients who had recovered from COVID-19. Mean age 63±12 (37-80) years with Male:Female ratio being 1.3:1. The mean duration between diagnosis of COVID-19 and development of symptoms of mucor was 23.5±10 (7–60) days. Rhino-orbital mucormycosis was the most typical presentation. Out of 30 cases, 28 cases (93.3%) were Type 2 Diabetes Mellitus, and 2 cases (6.6%)were nondiabetic. All patients received corticosteroids for the treatment of COVID-19. Trinity of COVID -19, Diabetes Mellitus, and Corticosteroid treatment was significant for the rise in mucormycosis cases. Mucormycosis is an invasive fungal infection and had seen a sudden surge during the second wave of COVID-19. In our study, most patients had a history of diabetes, and corticosteroid therapy with rhino-orbital mucormycosis was the most typical presentation. As the severity of the necrosis increases, the presence of fungal hyphae also increases, which leads to extensive destruction of tissue. Extra vigilance in immunosuppressed patients helps in reducing the morbidity and mortality due to mucormycosis in Post COVID era.